Perbandingan Konsep Pemikiran Pendidikan Islam K.H. Hasyim Asy’ari dan K.H. Ahmad Dahlan (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to understand the approach to Islamic education that is applied, and to find out the similarities and differences in views about Islamic education from KH's point of view. Ahmad Dahlan and KH. Hasyim Asy'ari. Both are persuasive specialists in Islamic education. KH. Ahmad Dahlan and KH. Hasyim Asy'ari has been successful in terms of tracking training. Among his thoughts in the development of education are speculation, speculation, tadaruj and progress, which are still involved in direction in the field of education as a whole. It is hoped that this study can provide an overview of the aims of KH's thinking. Ahmad Dahlan and KH. Hasyim Asy'ari is concerned with the idea of ​​Islamic teaching and understands the importance of the idea of ​​Islamic education both for general education. The research technique that the author uses is subjective qualitative through examination by collecting information and collecting diaries, logical articles, books and related sources related to the exploration point. From the investigations that have been carried out, it is clear that there is a connection with KH's ideas. Ahmad Dahlan and KH. Hasyim Asy'ari regarding Islamic education with general teaching, which, among other things, is illustrated by comparing the idea that the fundamental object of education is humans. Where humans consist of several important components that are interconnected and cannot be separated.